2002
DOI: 10.1007/pl00012517
|View full text |Cite
|
Sign up to set email alerts
|

Oligo-1,6-glucosidase and neopullulanase enzyme subfamilies from the α-amylase family defined by the fifth conserved sequence region

Abstract: The alpha-amylase enzyme family is the largest family of glycoside hydrolases. It contains almost 30 different enzyme specificities covering hydrolases, transferases and isomerases. Some of the enzyme specificities from the family are closely related, others less so. This study, based on the analysis of 79 amino acid sequences, postulates two subfamilies in the framework of the aamylase family: the oligo-1,6-glucosidase subfamily and the neopullulanase subfamily. The specific sequence in the fifth conserved se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 102 publications
3
91
0
Order By: Relevance
“…A multiple sequence alignment of top hits from BLASTP with LBA0264 and LBA1872 combined with SmGH13_31, characterized O16Gs, and enzymes from lactobacilli assigned to GH13_31 showed that LBA0264 aligns very well with SmGH13_31 in the conserved regions, which define pivotal ac- tive-site residues and region V ( Fig. 1), which is the ␣-1,6 specificity motif in the ␣-amylase family (clan GH-H according to the CAZy classification) (38). In addition, LBA0264, like SmGH13_31, has the shorter loop between conserved regions II and III, which defines the G16G subspecificity in GH13_31 (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multiple sequence alignment of top hits from BLASTP with LBA0264 and LBA1872 combined with SmGH13_31, characterized O16Gs, and enzymes from lactobacilli assigned to GH13_31 showed that LBA0264 aligns very well with SmGH13_31 in the conserved regions, which define pivotal ac- tive-site residues and region V ( Fig. 1), which is the ␣-1,6 specificity motif in the ␣-amylase family (clan GH-H according to the CAZy classification) (38). In addition, LBA0264, like SmGH13_31, has the shorter loop between conserved regions II and III, which defines the G16G subspecificity in GH13_31 (43).…”
Section: Resultsmentioning
confidence: 99%
“…Regions II and III, conserved in ␣-amylase family enzymes, encompass the catalytic groups and certain pivotal active-site residues (30). Region V defines the specificity motifs of 1,6-␣-glucosidases and neopullulanases (38). The catalytic residues are marked with arrows.…”
Section: Figmentioning
confidence: 99%
“…3) reflects the similarities and differences between clan GH-H and family GH31, and in addition contributes several novel findings to the evolutionary relationships known previously within the a-amylase family [10,[48][49][50][51]: (i) the circularly permuted GH70 family (glucosyltransferase and alternansucrase) is most closely related to the pullulanase subfamily of GH13 represented by pullulanase, isoamylase, maltooligosyl trehalose hydrolase and branching enzyme; (ii) the oligo-1,6-glucosidase subfamily (oligo-1,6-glucosidase, aglucosidase, dextran glucosidase, trehalose-6-phosphate hydrolase and isomaltulose synthase) is closest to the a-amylase and in a wider sense to the CGTase subfamily (CGTase and maltooligosaccharide-producing amylases); (iii) the neopullulanase subfamily (neopullulanase, cyclomaltodextrinase and maltogenic amylase) that may also contain amylopullulanase borders on a more diverse amylosucrase group including sucrose hydrolase, amylosucrase, trehalose synthase and 4-aglucanotransferase. The remaining four GH13 specificities, labelled as the sucrose phosphorylase group (maltooligosyl trehalose synthase, maltosyltransferase, sucrose phosphorylase and glucan debranching enzyme) are either on independent or long branches (Fig.…”
Section: Evolutionary Relationshipsmentioning
confidence: 67%
“…2) because typical maltogenic amylases (i.e. members of the neopullulanase subfamily) have a glutamate in that position as a part of the four-residue signature VANE (10).…”
Section: Resultsmentioning
confidence: 99%
“…Maltogenic amylase shares catalytic characteristics with neopullulanase and CDase, which catalyze the hydrolysis of cyclodextrins (CDs), pullulan, and acarbose, and which are collectively known as CD-hydrolyzing enzymes (9). These enzyme specificities were proposed to establish the so-called neopullulanase subfamily of the ␣-amylase family GH13 (10), which is currently classified as the subfamily GH13_20 (11). CD-hydrolyzing enzymes possess a common domain at the N terminus (N domain) that is involved in substrate binding through a domain-swapped homodimeric structure (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%